Pathological manifestation of Covid-19 in the oral cavity and the role of saliva in the spread of the virus - Zeynitdinova Ziyoda Askarovna (Zien Journals, 2023)
The COVID-19 pandemic is the current coronavirus infection pandemic caused by the SARSCoV-2 coronavirus [18]. The outbreak was first reported in Wuhan, China in December 2019 [11] on January 30, 2020. The World Health Organization declared the outbreak a public health emergency of international concern and a pandemic on March 11 [7, 5] As of April 5, 2021, over 132 million cases have been reported worldwide; more than 2.8 million people have died and more than 106.5 million have recovered.
Keywords: COVID-19; virus; oral cavity; saliva; droplets